PERANCANGAN PENUGASAN OPERASI DAN PEKERJA PADA STASIUN KERJA LINTAS PERAKITAN FINAL PESAWAT NC 212I PT DIRGANTARA INDONESIA - Alivia Yosefella, Sharene
PT Dirgantara Indonesia (PT DI) is a state-owned company specializing in aircraft manufacturing. The NC212i aircraft is one of the most demanded aircraft from all aircraft products produced by PT DI because of the completeness of its features with a demand of up to 6 aircraft units per year. The Final Assembly Line (FAL) Division is one of the divisions involved in the production process of the NC212i aircraft. It is responsible for carrying out the final assembly of the plane. Based on the statement of the Head of the FAL Division, the NC212i assembly line in the FAL hangar is currently unable to meet the annual production target. To complete 6 aircraft units per year, the FAL Division is expected to complete the assembly of each aircraft unit in 40 days. However, the actual cycle time is below the desired cycle time. The primary cause is due to the method of allocating ossembly operations that are not optimal and the lack of workers assigning method. Therefore, this study aims to develop a model of operations and workers’ assignment that corresponds to the characteristic of FAL Division’s assembly line to be then used in determining the design of operations and workers’ assignments that can meet the expected cycle time. This research developed mathematical models and heuristic algorithms to minimize the numbers of workers assigned. Practical constraints considered in the model are precedence constraint, cycle time, and the number and type of workers each operation requires. The search for a final solution with a heuristic algorithm resulted in a design that assigned 47 workers to carry out the operations that allocated on three workstations with a cycle time of 318.13 hours. The number of workers assigned in the solution is worth less than the number of workers in PT DI’s improvement design, which is 64 workers.